Cecília Meireles e os problemas da literatura infantil: uma abordagem discursiva - Ramanzini, Isis Cristina (2012)
The book Problems of Children's Literature, by Cecília Meireles, was first published in 1951, as a result of three lectures given by the author, in Belo Horizonte, in 1949, during a course sponsored by the Department of Education, the State of Minas Gerais. These conferences led to focus on broad themes work, but not separately analyze his nineteen chapters, but the intradiscourse that pervades. In the broadest sense of the book, we highlight the characteristics of children's literature, and the relationship between literature and writing. There are two main objectives of this research: to reveal, from the works concerned the placement of Cecília Meireles on children's literature in an important moment in the Brazilian educational history, and conclude the discursive ethos that the author constructs when dealing with themes of the book. To achieve the proposed objectives, we used the theoretical framework which includes the guidance that Maingueneau Dominique (2001, 2006a, 2008c) prints the AD French. We emphasize the discursive dimensions regarding paratopia, autoralidade and discursive ethos. Other concepts are also used, always reset depending on the perspective of our goals. The assays Lajolo (1982, 1996) and Zilberman (1994, 2001), two of the greatest experts in the field of children's literature in Brazil, are decisive contribution to this study. These works highlight the genesis of the genre, the historical context in which it develops, as well as the relationship of children's literature with the school institution. To broaden the base of theoretical and methodological research, we also consider the work of Pécaut (1990) who investigates the conviction of Brazilian intellectuals based in the responsibility of nation building in the first half of the twentieth century. The limits of the corpus of analysis takes into account the characterization of children's literature, according to the Problems of children's literature, the publications that refer to this work and proposals of the French AD that may be related to children's literature. Could not find any research (Google Academic and libraries of PUC-SP, USP, UNICAMP and UNESP) examining the Problems of children's literature book in the foundations of discourse analysis, the perspective developed by Dominique Maingueneau. Given the lack resides there, one of the contributions of this work. Finally, the analysis of conceptions of Cecília Meireles about children's literature in the context of AD French it seems fruitful and could help with the work of teachers of elementary school, the effect of a point of view "humanistic" about literature the child